Hepatitis C Virus Mediated Inhibition of miR‐181c Activates ATM Signaling and Promotes Hepatocyte Growth. Issue 3 (3rd November 2019) - Patra, Tapas; Meyer, Keith; Ray, Ratna B.; Ray, Ranjit
Abstract : Background and Aims: Hepatitis C virus (HCV) infection promotes hepatocyte growth and progress to hepatocellular carcinoma. We previously observed that HCV infection of hepatocytes transcriptionally down‐regulates miR‐181c expression through CCAAT/enhancer binding protein β (C/EBP‐β). Here, we examined the role of miR‐181c in the regulation of cell cycle progression in relation to HCV infection. In silico analysis suggested that ataxia‐telangiectasia mutated (ATM) protein, a protein kinase, is a direct target of miR‐181c. ATM is a central mediator of response for cellular DNA double‐strand break. Approach and Results: Our results demonstrated that ATM expression is higher in HCV‐infected hepatocytes and chronic HCV‐infected liver biopsy specimens. We have shown a direct interaction of miR‐181c with the 3′ untranslated region of ATM, and the presence of ATM in miR‐181c‐associated RNA‐induced silencing complex. Exogenous expression of miR‐181c inhibited ATM expression and activation of its downstream molecules, Chk2 and Akt. On the other hand, introduction of anti‐miR‐181c restored ATM and phosphorylated Akt. Furthermore, introduction of miR‐181c significantly inhibited phospho–cyclin‐dependent kinase 2 (CDK2) and cyclin‐A expression, arresting cell cycle progression, whereas overexpression of miR‐181c promoted apoptosis of HCV‐infected hepatocytes and can be inhibited by overexpression of ATM from a clone lacking miR‐181c binding sites. In addition, miR‐181c significantly regressed tumor growth in the xenograft human hepatocellular carcinoma mouse model. Conclusions: Together, our results suggest that HCV infection suppresses miR‐181c in hepatocytes, resulting in ATM activation and apoptosis inhibition for promotion of cell cycle progression. The results provide mechanistic insight into understanding the role of miR‐181c in HCV‐associated hepatocyte growth promotion, and may have the potential for therapeutic intervention.